Early imaging predictors of fetal cerebral ischemic injury in monochorionic twin pregnancy complicated by spontaneous single intrauterine death. (1st April 2022) - Shinar, S.; Harris, K.; Van Mieghem, T.; Lewi, L.; Morency, A. M.; Blaser, S.; Ryan, G.
ABSTRACT: Objective: Monochorionic twin pregnancies are at increased risk of single intrauterine death (sIUD) and subsequent brain injury in the surviving twin owing to shared placentation. We assessed the association between middle cerebral artery peak systolic velocity (MCA‐PSV) and cerebral injury on magnetic resonance imaging (MRI) and examined the association between cerebral findings on diffusion‐weighted imaging (DWI) and those on T2‐weighted imaging following spontaneous sIUD. Methods: This was a retrospective cohort study of monochorionic pregnancies complicated by spontaneous sIUD followed at a tertiary center between January 2008 and January 2020. Pregnancies with sIUD following laser treatment, those with selective feticide, double IUD occurring on the same day or sIUD before 14 weeks' gestation were excluded, as were cases in which MCA‐PSV was not measured or DWI‐MRI was not performed. The ability of MCA‐PSV Doppler to predict subsequent cerebral injury on MRI was assessed, and DWI findings were analyzed and compared with those on susceptibility‐weighted imaging (SWI) and T2‐weighted MRI to determine its diagnostic accuracy. Results: We assessed 64 monochorionic pregnancies complicated by spontaneous sIUD. Of these, 47 (73.4%) pregnancies underwent fetal brain MRI and met the inclusion criteria. Sixteen (34.0%) of these fetuses demonstrated cerebral injury on MRI. The median interval between the diagnosis of sIUD and MRI examination was 5 days. Fetuses with increased MCA‐PSV > 1.5 multiples of the median (MoM) following sIUD were significantly more likely to demonstrate cerebral injury on MRI than were those with normal MCA‐PSV (68.8% vs 38.7%; P = 0.05). The sensitivity and specificity of MCA‐PSV > 1.5 MoM for predicting cerebral injury on MRI were 68.8% (95% CI, 41.3–88.9%) and 61.3% (95% CI, 42.2–78.2%), respectively. Patterns of early cerebral injury on T2‐weighted and SWI‐MRI included acute or subacute tissue swelling ( n = 6), parenchymal atrophy ( n = 7), loss of cortical ribbon ( n = 1) and hemorrhage ( n = 8). Early MRI within approximately 2 weeks after the diagnosis of sIUD demonstrated abnormal DWI along with coexisting SWI and T2‐weighted sequelae in 56.3% (9/16) of cases. When DWI was normal and a second MRI examination was performed later ( n = 7), there were no ischemic changes evident on T2‐weighted imaging. Conclusions: Increased MCA‐PSV is associated with, but predicts poorly, cerebral injury after sIUD. Early MRI with DWI within approximately 2 weeks after the diagnosis of sIUD is valuable in identifying any cerebral injury. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Predictores de imágenes tempranas de lesión isquémica cerebral del feto en embarazo de gemelos monocoriónico complicado por muerte intrauterina única espontánea Objetivo: El embarazo gemelar monocorial tiene un mayor riesgo de muerte intrauterina única (MIU) y de lesión cerebral posterior en el gemelo superviviente debido a la placentación compartida. Se evaluó la asociación entre la velocidad sistólica máxima de la arteria cerebral media (VSM‐ACM) y las lesiones cerebrales en la imagen por resonancia magnética (IRM) y se examinó la asociación entre los hallazgos cerebrales en la imagen ponderada por difusión (IPD) y los de las imágenes ponderadas en T2 después de una MIU espontánea. Métodos: Este fue un estudio de cohorte retrospectivo de embarazos monocoriales complicados por MIU espontánea a los que se dio seguimiento en un centro de atención terciaria entre enero de 2008 y enero de 2020. Se excluyeron los embarazos con MIU después de un tratamiento con láser, aquellos con feticidio selectivo, con doble muerte intrauterina en el mismo día o con MIU antes de las 14 semanas de gestación, así como los casos en los que no se midió la VSM‐ACM o no se realizó una IPD‐IRM. Se evaluó la capacidad del Doppler de la VSM‐ACM para predecir lesiones cerebrales posteriores en la IRM, y se analizaron los hallazgos de la IPD, que se compararon con los de la imagen ponderada por susceptibilidad (IPS) y la IRM ponderada en T2 para determinar su precisión diagnóstica. Resultados: Se evaluaron 64 embarazos monocoriales complicados por MIU espontánea. De ellos, 47 (73, 4%) embarazos se sometieron a una IRM cerebral fetal y cumplieron los criterios de inclusión. Dieciséis (34, 0%) de estos fetos mostraron lesiones cerebrales en la IRM. La mediana del intervalo entre el diagnóstico de MIU y el examen por IRM fue de 5 días. Los fetos con un aumento en la VSM‐ACM >1, 5 múltiplos de la mediana (MdM) tras una MIU fueron significativamente más propensos a demostrar una lesión cerebral en la IRM que los que tuvieron una VSM‐ACM normal (68, 8% frente a 38, 7% P=0, 05). La sensibilidad y la especificidad de la VSM‐ACM >1, 5 MdM para predecir lesiones cerebrales en la IRM fueron del 68, 8% (IC 95%, 41, 3–88, 9%) y del 61, 3% (IC 95%, 42, 2–78, 2%), respectivamente. Entre los patrones de lesiones cerebrales tempranas en la IRM ponderada en T2 y en la IPS‐IRM estuvieron la inflamación de tejidos aguda o subaguda (n=6), atrofia del parénquima (n=7), pérdida de cinta cortical (n=1) y hemorragia (n=8). La IRM temprana a las 2 semanas aproximadamente tras el diagnóstico de MIU demostró una IPD anómala junto con secuelas coexistentes en la IPS y en la ponderación en T2 en el 56, 3% (9/16) de los casos. Cuando la IPD fue normal y se realizó después un segundo examen por IRM (n=7), no hubo cambios isquémicos evidentes en las imágenes ponderadas en T2. Conclusiones: El aumento de la VSM‐ACM está asociado a lesiones cerebrales después de una MIU, pero es un mal predictor. La IRM temprana con IPD al cabo de 2 semanas aproximadamente tras el diagnóstico de MIU es valiosa para identificar cualquier lesión cerebral. 摘要: 对由自发性双胎一胎胎死宫内造成并发症的单绒毛膜双胎妊娠的早期成像预测胎儿颅脑缺血性损伤 目的: 单绒毛膜双胎妊娠有双胎一胎胎死宫内(sIUD)的增加性风险，并且由于分享胎盘，此后可对存活下来的双胎之一造成脑损伤。我们用磁共振成像(MRI)评估了大脑中动脉峰值流速(MCA‐PSV)与颅脑损伤之间的关联，以及继自发性sIUD后用磁共振扩散加权成像(DWI)的脑部发现和 用T2加权成像的脑部发现之间的关联。 方法: 这是于2008年1月至2020年1月间在一家三级中心随访由自发性sIUD造成并发症的单绒毛膜双胎妊娠的一项回顾性队列研究。不包含激光治疗后有sIUD的妊娠、选择性减胎术的妊娠、同一天的双胎IUD或孕14周前的sIUD，也不包含未测量MCA‐PSV或未进行DWI‐MRI的病例。在MRI上MCA‐PSV多普勒预测后续颅脑损伤的能力得到了评估，而且分析了DWI调查结果并与磁敏感加权成像(SWI)和T2加权成像的调查结果进行比较，来确定其诊断准确性。 结果: 我们评估了64例由自发性sIUD造成并发症的单绒毛膜双胎妊娠。其中有47例(73.4%)进行了胎脑MRI并满足了入选标准。其中有16个胎儿(34.0%)在MRI上显示出颅脑损伤。sIUD诊断与MRI检查之间的时间间隔中间数为5天。与MCA‐PSV正常的胎儿相比，那些继sIUD后升高的MCA‐PSV>1.5中位倍数(MoM)的胎儿更显著地有可能在MRI显示出颅脑损伤(68.8% 对 38.7%; P=0.05)。MCA‐PSV >1.5MoM预测MRI上颅脑损伤的敏感性与特异性分别为68.8%(95% CI, 41.3–88.9%)和61.3%(95% CI, 42.2–78.2%)。在T2加权成像和SWI‐MRI中早期颅脑损伤的模式包括急性或亚急性组织肿胀(n=6)、实质性萎缩(n=7)、皮质丧失(n=1)和出血(n=8)。在56.3%(9/16)的病例中，sIUD诊断后2周内左右的早期MRI显示出DWI、共存SWI和T2加权成像的并发症。当DWI正常并在此后进行了第二次MRI检查(n=7)，T2加权成像上未显示局部缺血变化的迹象。 结论: 增加的MCA‐PSV与sIUD后颅脑损伤相关，但预测不佳。sIUD诊断后2周内左右的早期MRI和DWI对识别任何颅脑损害都有价值。